2003
DOI: 10.1093/jnci/djg046
|View full text |Cite
|
Sign up to set email alerts
|

Extended Follow-Up of a Cohort of British Chemical Workers Exposed to Formaldehyde

Abstract: The evidence for human carcinogenicity of formaldehyde remains unconvincing. Although a small effect on sino-nasal or nasopharyngeal cancer cannot be ruled out, a possible increase in the risk of lung cancer is a greater concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
150
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 21 publications
2
150
1
5
Order By: Relevance
“…Findings from these studies did not strongly support an effect of formaldehyde on lung cancer risk. Statistically significant positive associations were observed in only 2 of the 14 cohort studies (2, 6 -19): in the subgroup of wood-related workers from a general US population cohort (11) and a large occupational cohort of British workers (10). For three cohorts, results showed positive associations although not statistically Mahboubi et al which subgroups defined by smoking status were examined (6,23) where differences in the formaldehyde-lung cancer associations were not apparent.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Findings from these studies did not strongly support an effect of formaldehyde on lung cancer risk. Statistically significant positive associations were observed in only 2 of the 14 cohort studies (2, 6 -19): in the subgroup of wood-related workers from a general US population cohort (11) and a large occupational cohort of British workers (10). For three cohorts, results showed positive associations although not statistically Mahboubi et al which subgroups defined by smoking status were examined (6,23) where differences in the formaldehyde-lung cancer associations were not apparent.…”
Section: Discussionmentioning
confidence: 96%
“…Both were among the case-control investigations with the largest numbers of exposed cases. Among the same 23 studies, only a few further analyzed each of the more refined measures of formaldehyde exposure, including exposure level (2,10,12,27), lifetime cumulative exposure (2,6,23,28), duration of exposure (2,6,7,9,10,18,24), time since first exposure (6,7,18), and peak exposure (2). However, even when formaldehyde exposure was analyzed using these more detailed metrics, increased risks were observed only in two studies with high exposure level (10) and longer exposure duration (24), and a decreased risk was reported with longer duration in another (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18] Since then, some studies on humans have suggested that formaldehyde exposure is associated with certain types of cancer. [19][20][21] When exposed to formaldehyde, some individuals may experience various short-term effects. Formaldehyde has been classifi ed as a known human carcinogen (cancer-causing substance) by the International Agency for Research on Cancer and as a probable human carcinogen by the United States Environmental Protection Agency.…”
Section: Methanolic Extract Of Malus Domestica Mitigates Formalin -Inmentioning
confidence: 99%